GENDER AND BEHAVIOUR MANAGEMENT AS CORRELATES OF READING AND WRITING IN PUPILS IN ORU EAST LOCAL GOVERNMENT AREA, IMO STATE - Onwuka, Lilian Nwanneka; Orji, Amarachi (Journal of Early Childhood and Primary Education, 2025)
This study investigates the relationship between teachers' gender, classroom behaviour management, pupils’ reading and writing abilities in Oru East Local Government Area, Imo State. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. The study adopted the correlation survey research design. The sample for the study involved 377 respondents comprising 47 teachers and 330 pupils in 20 primary schools in the area. The instruments for data collection were two: Classroom Management Practices Survey (CMPS) and Pupils’ Reading and Writing Achievement Schedule (PRWAS). The CMPS and PRWAS were subjected to face validity by three validates. The reliability of the instruments was determined using the Cronbach Alpha. Coefficients for .73 and .82 for PRWAS. The method for data collection was the direct delivery approach. Linear Regression was used to test hypotheses at 0.05 level of significance. The correlation matrix that teachers’ gender has moderate relationship with reading and writing among primary schools’ pupils, and a moderate relationship between teachers’ behaviour management and pupils’ performance in reading and writing skills. The null hypothesis is rejected and implies that teachers’ gender has a significant relationship with pupils’ performance in reading and writing in primary schools. Similarly, behaviour management has a significant relationship with pupils; performance in reading and writing in primary schools. Based on these results, the researcher recommends targeted professional development for teachers in behaviour management, promotion of gender-sensitive teaching practices, and the implementation of data-driven educational strategies to improve pupils’ performance. These measures aim to create a more supportive and equitable learning environment, thereby improving literacy skills among pupils.
Keywords: Gender; Behaviour Management; Teachers; Pupil; Performance; Reading Skill; Writing Skill